Associations of childhood unintentional injuries with maternal emotional status during COVID-19 - Xiangrong Guo; Hui Hua; Jian Xu; Zhiwei Liu (BMC, 2021)
Abstract Background To explore the characteristics of unintentional childhood-injury during the COVID-19 pandemic and assess the association of unintentional-injury with maternal emotional status. Methods A cross-sectional survey was conducted with a convenience sample of 1300 children under 12-years-old from 21 schools (including nurseries/ kindergartens/ primary schools) in Wuhan and Shanghai during March to April 2020, and the mothers completed questionnaires online. Self-rating Depression/Anxiety Scales were used to evaluate maternal emotional status, questions on child unintentional-injury were based on the International-Statistical-Classification-of-Diseases-and-Related-Health-Problems-version-10 (ICD-10), and a total of 11 kinds of unintentional injuries were inquired. Information on socio-demographic and family-background factors was also collected. Results The children of 0-4, 5-9, and 10-12 years accounted for 29.2, 55.2 and 15.6%, respectively, the unintentional-injury rates were 10.29, 4.18 and 3.45%, respectively (P < 0.001), and boys had higher rates than girls. The three leading causes included "being struck by/against", falls and animal bites (traffic-injury accounted for a small proportion). Lower maternal educational, living in suburban/rural (vs. urban) areas, grandparents (vs. mothers) being main caregivers, more child exposure to secondhand smoke, close relatives being suspected/ confirmed COVID-19 cases were associated with a higher risk of child unintentional-injury. After adjusting for related confounders, higher maternal depression levels were associated with a higher risk of unintentional injury. Conclusions The characteristics of unintentional childhood injury were different from those in non-pandemic periods. The main causes, risk factors and the association of unintentional injury with maternal depression deserve attention for development of effective measures for preventing children from unintentional injury during COVID-19 pandemic. Graphical abstract